L'epistolario latino dell'umanista Bartolomeo Fonzio, la sua genesi e le sue redazioni: tra autobiografia, storia e tensioni culturali (Quaderni di Gargnano, 2018)
The article casts light upon the genesis of Bartolomeo Fonzio’s Epistolarum libri and explores the different editions of the letterbooks over the years. By comparing significant specimens of the writings, the author reveals Bartolomeo’s meticulous working methods and continuous labor limae as he polished and honed his style and revised his texts to reflect new historical circumstances.
Keywords: Fonzio; Humanistic epistolography; manuscript tradition